The Determinants Of Equity Based Compensation: A Bidimensional Validity Of The Agency Theory - Mehdi, Bouras; Mohamed Imen, Gallali (Asian Academy of Management (AAM), 2014)
Previous studies have tried to make a comparative analysis between the market-oriented system and the mixed governance system on the determinants of stock option awards for managers; however, these studies exhibit some failures that must be overcome. In addition, we note the absence of studies addressing the validity of the agency theory on the determinants of equity-based compensation in times of instability or crisis. We used a sample of 159 French companies and 203 US companies for the period spanning 2002 to 2010. The results of the present study support the conclusion that the variables measuring the size of the firm, growth opportunity, debt, management and control functions, size of the board, and ownership concentration explain the decision to grant equity-based compensation, regardless of the sample and period considered. Using a variable representing the presence of institutional investors, we show that this type of investor is only involved in controlling the leader in the French case, during a period of financial instability.